POTENSI EKSTRAK ETANOL BATANG WOLE WOE ASAL KABUPATEN HALMAHERA TENGAH SEBAGAI ANTIBAKTERI MENGGUNAKAN METODE KLT-BIOAUTOGRAFI - Fitriana, Fitriana; Amirah, Sitti; Rahman, Safriani; Rusli, Rusli; Nurung, Ayyub Harly (As-Syifaa Jurnal Farmasi, 2023)
The development of natural materials both from plants and from other materials as traditional medicines can be done by taking habits from the community in utilizing natural materials empirically. The wole woe plant is one of the plants that comes from the forest and grows wildly and is empirically used as a traditional medicine by the Weda community in Central Halmahera Regency. This study aims to see the chromatogram of wole woe stem extract and the group of chemical components that have potential as antibacterial using KLT-Bioautography method. The results of the chromatogram of the ethanol extract of wole woe stem, obtained 6 spots and there are 2 spots with rf values of 0.65 and 0.09 which have activity against bacteria Staphylococcus aureus, Streptococcus mutans, Bacillus subtilis and Pseudomonas aeruginosa. The results of the identification of chemical components using specific reagents, obtained chemical groups of anthraquinones, flavonoids, phenolics and alkaloids have potential as antibacterial, so that the ethanol extract of wole woe stem has potential as antibacterial.